2019
DOI: 10.1139/cjfr-2018-0246
|View full text |Cite
|
Sign up to set email alerts
|

Additive biomass equations for slash pine trees: comparing three modeling approaches

Abstract: Both aggregative and disaggregative strategies were used to develop additive nonlinear biomass equations for slash pine (Pinus elliottii Engelm. var. elliottii) trees in the southeastern United States. In the aggregative approach, the total tree biomass equation was specified by aggregating the expectations of component biomass models, and their parameters were estimated by jointly fitting all component and total biomass equations using weighted nonlinear seemingly unrelated regression (NSUR) (SUR1) or by join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…Among these methods of parameter estimation, nonlinear seemingly unrelated regression (NSUR) and seemingly unrelated regression (SUR) are the most widely used. An advantage of SUR and NSUR is the low variance of the total stand biomass model because of their own predictor variables and weighting function account for heteroscedasticity, which makes SUR and NSUR popular methods for parameter estimation in nonlinear and linear stand biomass equations [11][12][13][14]30]. Although several researchers have proposed the inclusion of additivity, it has often been ignored in some stand biomass models [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods of parameter estimation, nonlinear seemingly unrelated regression (NSUR) and seemingly unrelated regression (SUR) are the most widely used. An advantage of SUR and NSUR is the low variance of the total stand biomass model because of their own predictor variables and weighting function account for heteroscedasticity, which makes SUR and NSUR popular methods for parameter estimation in nonlinear and linear stand biomass equations [11][12][13][14]30]. Although several researchers have proposed the inclusion of additivity, it has often been ignored in some stand biomass models [8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the aggregative approach, the total tree biomass equation is specifi ed by aggregating the expectations of component biomass models, and their parameters were estimated by a joint selection of the equations for all the components and the total biomass using a weighted nonlinear, apparently unrelated regression (NSUR), or by a joint selection of the equations of the component biomass using weighted NSUR. In addition, several researches (Parresol, 1999(Parresol, , 2001Usoltsev et al, 2016Usoltsev et al, , 2017Zhao et al, 2019) noted that there is no single system to predict all tree biomass components and total tree biomass. Consequently, comparative analyses between the estimated biomass means of the total AGB using our predicted best models for Scots pine showed rather similar means, where diff erence between the two means amounted to only 24.7 kg (8.5%).…”
Section: Discussionmentioning
confidence: 99%
“…We used allometric equations (Lambert et al 2005) to obtain estimates of biomass that were then converted to carbon. Component ratios (Heath et al 2009) have been shown to be less variable than the use of allometric equations (however, see the recent work by Zhao et al (2018), which indicated that component ratio equation did not prove to be less variable than allometric equations for components). Incorporating a component ratio approach into our bigBAF sampling scheme may reduce the CVs associated with the various carbon components and reduce the costs required to estimate these at the accuracies required by carbon offset programs.…”
Section: Discussionmentioning
confidence: 99%